UTILIZATION OF OYSTER MUSHROOM BAGLOG WASTE AS ORGANIC COMPOST IN THE PROSPEROUS LIME OYSTER MUSHROOM CULTIVATION GROUP, LIMAU MANIS VILLAGE, PAUH DISTRICT - Meutia, Risa; Permata, Deivy Andika; Asben, Alfi (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2022)
The LMS oyster mushroom cultivation group consists of 31 people. Each member has a kumbung with a capacity of 2000-4000 baglog. The problems that arise from the cultivation of oyster mushrooms are: Oyster mushroom baglog waste that is no longer productive is wasted and becomes environmental pollution. Besides polluting the environment, it can also be a polluter for baglogs that are still productive. One effort that can be done is to process it into compost. Unproductive baglog processing can increase added value. Utilization of compost can be applied to vegetable crops and ornamental plants. Processing compost from baglog that is not productive is also beneficial in preserving the environment.